DETERMINANTS OF ACCOUNTING INFORMATION USE IN MICRO, SMALL AND MEDIUM ENTERPRISES (SMES) - Wahyuningsih, Titi; Yuliani, Nur Laila; Purwantini, Anissa Hakim; Susanto, Barkah; Utami, Pranita Siska (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
The use of accounting information can help businesses in facing business competition. Accounting information is useful as a consideration in making decisions. The existence of accounting information business actors can find out profits. This study aims to examine the effect of education, business size, length of business, accounting training and accounting knowledge on the use of accounting information in MSMEs in Magelang Regency. This study uses a sample of MSMEs in Magelang Regency that have been established for at least 1 year. The number of samples in this study were 125 respondents, based on the slovin formula, namely Micro, Small and Medium Enterprises (MSMEs) in Magelang Regency that use accounting information either manually or by computer. Hypothesis testing in this study used multiple linear regression with the SPSS application. The results of this study indicate that education, length of business and accounting knowledge have a positive effect on the use of accounting information. While business size and accounting training have no effect on the use of accounting information.